How are nicotine vaping products represented to pharmacists? A content analysis of Australian pharmacy news sources. (20th April 2020) - Erku, Daniel A; Zhang, Rebecca; Gartner, Coral E; Morphett, Kylie; Steadman, Kathryn J
Abstract: Background: With the growing popularity and use of nicotine vaping products (NVPs), it is important that pharmacists have evidence-based information in order to provide guidance to their customers. The news media can play an important role in shaping how pharmacists think, feel and act regarding NVPs. This paper examines how NVPs are portrayed and framed in Australian pharmacy news sources. Methods: Four leading Australian online pharmacy professional news sources were searched for articles published between 2007 and August 2019. A combination of qualitative and quantitative methods was employed to explore how the safety, efficacy and regulation of NVPs was communicated. Results: We identified and analysed 103 relevant articles. Academic research findings and/or expert opinions were either cited or referenced most often, appearing in a total of 59% of articles analysed, followed by government sources quoted in 41% of articles. Health effects and safety issues of NVPs were the most frequently mentioned topic appearing in a total of 79% of the stories, followed by NVP-related regulatory issues (47%). The majority of NVP-related articles were framed in a loss rather than gain contexts, with more emphasis given to the concern that NVPs have the potential to addict youth to nicotine and undermine Australia's progress in tobacco control. Conclusion: Australian pharmacy news media have more often reported the potential risks than the potential benefits of NVPs. Such portrayal is likely to contribute to misperceptions about the relative harm of NVPs. Pharmacy staff need access to unbiased and evidence-based guidance on how to handle customer enquiries regarding NVPs.